ANALISIS TINGKAT KEBERHASILAN PENGAMBILAN KEPUTUSAN DAN EKSEKUSI MELALUI SCANNING PEMAIN PSB BOGOR U-17 PIALA SOERATIN NASIONAL - Nanda Agung Saputra, Mishbahudin; Izzuddin, Deden Akbar; Wijaya, Habibi Hadi (Fakultas Ilmu Keolahragaan Unimed, 2025)
This study aims to analyze the relationship between scanning and the success of decision-making and execution in PSB Bogor U-17 players in the quarter-finals of the National Soeratin Cup. The method used is descriptive qualitative with observation through match videos. The sample consisted of 15 players, with recording of scanning frequency and evaluation of technical success such as passing, control, dribbling, and shooting. The results show that the higher the scanning frequency, the better the decision-making and technical execution. The three players with the highest scanning frequency were Muhammad Gilang Maulana (63 times), Reski Agya Nugraha (62), and Oka Syafaruddin Bachrum (61), who also recorded high technical contributions. Muhammad Gilang recorded the highest success rate of 78%. This study concludes that scanning plays an important role in improving player performance and recommends scanning training in youth player development to support playing intelligence and effectiveness on the field.